Desain Alat Pengendali Nilai Redaman Attenuator Digital Radio Frekunsi (RF) Pada Sistem Komunikasi Melalui Jaringan TCP/IP - Pristianto, Eko Joni; Hardiati, Sri (Pusat Penelitian Informatika - LIPI, 2011)
This paper presents interface circuit design between personal computer (PC) and a digital attenuator radio frequency (RF). This system is functioned to control the amplitude attenuation value or strength the RF analog signal until resulting a desired signal level into RF communication systems. The interface circuit will replace a manual digital attenuator controlled system by switch. In this design delivery data system by TCP/IP and microcontroller are used to be input-output device and software designed with basic langguage. The interface circutiÂ design are purposed to control attenuation of the RF digital attenuation through PC with the result that can controlling systems from long distance.